2024
DOI: 10.1021/acs.chemrev.3c00148
|View full text |Cite
|
Sign up to set email alerts
|

The Enigma of Methanol Synthesis by Cu/ZnO/Al2O3-Based Catalysts

Arik Beck,
Mark A. Newton,
Leon G. A. van de Water
et al.

Abstract: The activity and durability of the Cu/ZnO/Al 2 O 3 (CZA) catalyst formulation for methanol synthesis from CO/CO 2 /H 2 feeds far exceed the sum of its individual components. As such, this ternary catalytic system is a prime example of synergy in catalysis, one that has been employed for the large scale commercial production of methanol since its inception in the mid 1960s with precious little alteration to its original formulation. Methanol is a key building block of the chemical industry. It is also an attrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 588 publications
(2,725 reference statements)
0
2
0
Order By: Relevance
“…Since the surface of the catalyst responded to the presence of CO 2 and H 2 , morphological changes were observed during CO 2 hydrogenation that have not been detected previously in E-TEM images collected while exposing metal/oxide catalysts to either plain H 2 or CO oxidation conditions. ,, These morphological changes may be responsible for the difficulties reported when establishing the active phase for catalysts used in CO 2 hydrogenation. ,,,, The E-TEM results in Figures , , , S4 and S5 showed that the surface morphology of the Cu@TiO x catalyst was far from being static and evolved with changes in the chemical environment and temperature. The inverse oxide/metal configuration was a dynamic entity with the distribution of TiO x aggregates on top of the copper particles changing in different ways in the presence of H 2 , O 2 or CO 2 .…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Since the surface of the catalyst responded to the presence of CO 2 and H 2 , morphological changes were observed during CO 2 hydrogenation that have not been detected previously in E-TEM images collected while exposing metal/oxide catalysts to either plain H 2 or CO oxidation conditions. ,, These morphological changes may be responsible for the difficulties reported when establishing the active phase for catalysts used in CO 2 hydrogenation. ,,,, The E-TEM results in Figures , , , S4 and S5 showed that the surface morphology of the Cu@TiO x catalyst was far from being static and evolved with changes in the chemical environment and temperature. The inverse oxide/metal configuration was a dynamic entity with the distribution of TiO x aggregates on top of the copper particles changing in different ways in the presence of H 2 , O 2 or CO 2 .…”
Section: Resultsmentioning
confidence: 83%
“…Nowadays, the trapping and conversion of CO 2 is a major issue in environmental chemistry. Metal-oxide interfaces are frequently used for the catalytic conversion of CO 2 into into fuels and high-value chemicals. There have been a lot of studies focused on identifying the active phase of metal/oxide catalysts that are active for the hydrogenation of CO 2 to methanol. , High-resolution transmission electron microscopy (HR-TEM) has been used to study the morphology of powder Cu/ZnO/Al 2 O 3 catalysts after exposure to pure H 2 or the CO 2 /H 2 reactants. , The microscopy results showed that the active phase of the catalyst involved an inverse oxide/metal configuration produced as a consequence of strong metal–support interactions. , The addition of ZnO to copper opens new reaction channels for the dissociation of H 2 and conversion of CO 2 to CO or oxygenates. ,, Cu–TiO 2 interfaces also display superior activity and selectivity during CO 2 hydrogenation and are receiving a lot of attention. They can exhibit a lot of interesting features. In particular, the trapping of Cu centers into the titania lattice can prevent admetal sintering and improve long-term activity and stability for CO 2 hydrogenation . Furthermore, the formation of Cu–Ti–O x units can facilitate H 2 dissociation and the hydrogenation of CO 2 into oxygenates. , Recent theoretical calculations have predicted that a Cu/TiO 2 interface binds CO 2 much better than isolated copper or titania, and spontaneous dissociation of CO 2 to CO has been observed on defective surface of Cu­(I)/TiO 2– x nanoparticles at room temperature .…”
Section: Introductionmentioning
confidence: 99%